Fitness profiles of highly trained female futsal players according to their playing positions - Albalad-Aiguabella, R.; Mainer-Pardos, E.; Roso-Moliner, A.; Lozano, D.; Vicente-Rodríguez, G.; Muniz-Pardos, B. (International Journal of Sports Physiology and Performance, 2025)
Purpose: Although women`s futsal has experienced great growth recently, few studies have analyzed the physical profiles of female futsal players. The objectives of this study were to determine the physical and anthropometric characteristics in elite women`s futsal using laboratory and field tests and to analyze the differences between the different playing positions.